Design, synthesis, and biological activity of bicyclic radester analogues as Hsp90 inhibitors - Jadhav, Vinod D. (2009)
Bicyclic radester analogues have been synthesized and evaluated for Hsp90 inhibitory activity. These analogues induce concentration-dependent degradation of Hsp90-dependent client proteins with the six-membered bicyclic analogues manifesting increased activity versus the five-membered counterparts.